Structure and function of CYP108D1 from Novosphingobium aromaticivorans DSM12444: an aromatic hydrocarbon-binding P450 enzyme. - Bell, S; Yang, W; Yorke, J; Zhou, W; Wang, H; Harmer, J; Copley, R; Zhang, A; Zhou, R; Bartlam, M; Rao, Z; Wong, L (2012)
CYP108D1 from Novosphingobium aromaticivorans DSM12444 binds a range of aromatic hydrocarbons such as phenanthrene, biphenyl and phenylcyclohexane. Its structure, which is reported here at 2.2 Å resolution, is closely related to that of CYP108A1 (P450terp), an α-terpineol-oxidizing enzyme. The compositions and structures of the active sites of these two enzymes are very similar; the most significant changes are the replacement of Glu77 and Thr103 in CYP108A1 by Thr79 and Val105 in CYP108D1. Other residue differences lead to a larger and more hydrophobic access channel in CYP108D1. These structural features are likely to account for the weaker α-terpineol binding by CYP108D1 and, when combined with the presence of three hydrophobic phenylalanine residues in the active site, promote the binding of aromatic hydrocarbons. The haem-proximal surface of CYP108D1 shows a different charge distribution and topology to those of CYP101D1, CYP101A1 and CYP108A1, including a pronounced kink in the proximal loop of CYP108D1, which may result in poor complementarity with the [2Fe-2S] ferredoxins Arx, putidaredoxin and terpredoxin that are the respective redox partners of these three P450 enzymes. The unexpectedly low reduction potential of phenylcyclohexane-bound CYP108D1 (-401 mV) may also contribute to the low activity observed with these ferredoxins. CYP108D1 appears to function as an aromatic hydrocarbon hydroxylase that requires a different electron-transfer cofactor protein.